Evolution, biogenesis, expression, and target predictions of a substantially expanded set of Drosophila microRNAs - Ruby, J. Graham; Stark, Alexander; Johnston, Wendy K.; Kellis, Manolis; Bartel, David P.; Lai, Eric C. (Genome Research, 2007)
MicroRNA (miRNA) genes give rise to small regulatory RNAs in a wide variety of organisms. We used computational methods to predict miRNAs conserved among Drosophila species and large-scale sequencing of small RNAs from Drosophila melanogaster to experimentally confirm and complement these predictions. In addition to validating 20 of our top 45 predictions for novel miRNA loci, the large-scale sequencing identified many miRNAs that had not been predicted. In total, 59 novel genes were identified, increasing our tally of confirmed fly miRNAs to 148. The large-scale sequencing also refined the identities of previously known miRNAs and provided insights into their biogenesis and expression. Many miRNAs were expressed in particular developmental contexts, with a large cohort of miRNAs expressed primarily in imaginal discs. Conserved miRNAs typically were expressed more broadly and robustly than were nonconserved miRNAs, and those conserved miRNAs with more restricted expression tended to have fewer predicted targets than those expressed more broadly. Predicted targets for the expanded set of microRNAs substantially increased and revised the miRNA-target relationships that appear conserved among the fly species. Insights were also provided into miRNA gene evolution, including evidence for emergent regulatory function deriving from the opposite arm of the miRNA hairpin, exemplified by mir-10, and even the opposite strand of the DNA, exemplified by mir-iab-4.